2007
DOI: 10.1590/s1413-81232007000600034
|View full text |Cite
|
Sign up to set email alerts
|

Consentimento livre e esclarecido em odontologia nos hospitais públicos do Distrito Federal

Abstract: Personal powers of decision and individuality must be respected, grounded on autonomy expressed through informed consent. This paper examines data on the actual use of informed consent in public hospitals in Brazil's Federal District. A questionnaire was completed by dentists in public hospitals, and its findings show that verbal informed consent is obtained at the start of treatment in most of the hospitals. Errors were noted in the use and conceptualization of informed consent. Failing to distinguish between… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
10

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 1 publication
0
2
0
10
Order By: Relevance
“…Federal foram avaliados quanto aos princípios bioéticos de serviço; oito hospitais fizeram parte da amostra, apenas um mencionou não ter prontuário próprio a odontologia para o paciente, assim como uma instituição não utilizava o TCLE, sendo duas de forma escrita e cinco de maneira informal. Embora haja busca pelo princípio da autonomia do paciente, mesmo que verbalmente, os autores mencionam a necessidade dos profissionais envolvidos se aprofundarem no assunto (MALUF et al 2007).…”
Section: Os Hospitais Públicos Que Prestam Atendimento Odontológico Eunclassified
“…Federal foram avaliados quanto aos princípios bioéticos de serviço; oito hospitais fizeram parte da amostra, apenas um mencionou não ter prontuário próprio a odontologia para o paciente, assim como uma instituição não utilizava o TCLE, sendo duas de forma escrita e cinco de maneira informal. Embora haja busca pelo princípio da autonomia do paciente, mesmo que verbalmente, os autores mencionam a necessidade dos profissionais envolvidos se aprofundarem no assunto (MALUF et al 2007).…”
Section: Os Hospitais Públicos Que Prestam Atendimento Odontológico Eunclassified
“…The informed consent form in hospitals of federal districts was investigated by Maluf et al [19], and it was demonstrated that the informed consent form is presented verbally to the patients at the beginning of the treatments, without prior clarification of the treatment to be performed. These authors demonstrated that dentists working in the public hospital network needed a deepening of the bioethical foundations to apply the informed consent form effectively during their integrated clinical research procedures.…”
Section: Articlementioning
confidence: 99%
“…In the studies of Maluf et al [19] it was verified that the individuals included in the research do not have autonomy in the treatment decision, to which they will be submitted. According to Closet [8] the principle of autonomy guides people to self-govern, recognizing the patient's control over life itself.…”
Section: Articlementioning
confidence: 99%
“…Os autores concluíram que a utilização de forma consciente deste documento leva não só ao respeito à autonomia dos pacientes, como também a uma maior eficácia no exercício da beneficência para com o paciente. 20 A utilização de instrumentos que visem assegurar a autonomia dos indivíduos pode ainda em casos de pesquisas com seres humanos, garantir a aplicação das normativas vigentes no Brasil.…”
unclassified